(untitled) (Journal of Contemporary Philology, 2021)
(Old Church Slavonic Grammar by Emilija Crvenkovska, printed by Blaže Koneski Faculty of Philology, Ss. Cyril and Methodius University in Skopje, 2021, 234 pages)